2017
DOI: 10.1021/acsami.7b04603
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Block Polymer Thin Films Functionalized with Bio-Inspired Ligands for the Efficient Capture of Heavy Metal Ions from Water

Abstract: Heavy metal contamination of water supplies poses a serious threat to public health, prompting the development of novel and sustainable treatment technologies. One promising approach is to molecularly engineer the chemical affinity of a material for the targeted removal of specific molecules from solution. In this work, nanoporous polymer thin films generated from tailor-made block polymers were functionalized with the bio-inspired moieties glutathione and cysteamine for the removal of heavy metal ions, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…5 and fig. S8), making this system a starting platform for other applications, such as adsorption and removal of heavy metals ( 35 , 36 ), which require hydrophilic materials or further functionalization. Because of the presence of carboxylic groups and the unique morphology, a targeted application could be to use the now converted PS- b -PAA isotropic film as a scaffold to grow porous inorganic materials ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 and fig. S8), making this system a starting platform for other applications, such as adsorption and removal of heavy metals ( 35 , 36 ), which require hydrophilic materials or further functionalization. Because of the presence of carboxylic groups and the unique morphology, a targeted application could be to use the now converted PS- b -PAA isotropic film as a scaffold to grow porous inorganic materials ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a previous study demonstrated the coupling of the small molecule, cysteamine, as well as the peptide, glutathione, to the pore wall. 125 Both chemistries were able to remove more than 98% of the lead ions in a 50 ppm feed solution via selective binding between the metal ions and the thiol groups of the two ligands. Similar chemical flexibility can be realized in many precursor systems.…”
Section: Modifying the Pore Wall Chemistry For Advanced Solute Separamentioning
confidence: 99%
“…Adsorptive nanoporous membranes are an emerging class of nanomaterials whose promise arises from their multifunctional nanostructure, which is controlled during synthesis to target specific contaminants such as lead. 28 Once depleted, these membranes can be reused after regeneration using external stimuli such as pH swings. 28,29 Their ability to selectively extract contaminants from water and their reusability makes adsorptive nanoporous membranes an attractive option for integration into FFP water treatment systems.…”
Section: Introductionmentioning
confidence: 99%